Lean manufacturing best practices in SMEs - Rose, A. M. N.; Md Deros, Baba; Ab. Rahman, Mohd Nizam; Nordin, Norani (2011)
Last two decades had witnessed explosion of researches into the area of manufacturing improvement such as lean manufacturing, total quality management, total productive maintenance and their application within various manufacturing companies such as automotives, electronics, plastics components and etc.It was proven that lean manufacturing was considered as the best manufacturing system in the 21st century.A comprehensive literature review was conducted to get necessary lean information.The review is focused on SME definitions and characteristics.This is followed by reviewing the lean practices and discusses them based on SMEs’ capabilities. The aim of this paper is to present feasible lean practices for lean implementation in SMEs.There are seventeen lean practices which could be considered are feasible and relevant to the SME characteristics.The proposed practices were based on three categories; least investment, feasible to apply in SME and recommended by researchers